2000
DOI: 10.1017/s0027763000007212
|View full text |Cite
|
Sign up to set email alerts
|

Integers free of small prime factors in arithmetic progressions

Abstract: Abstract. For real x ≥ y ≥ 2 and positive integers a, q, let Φ(x, y; a, q) denote the number of positive integers ≤ x, free of prime factors ≤ y and satisfy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…holds uniformly in the range 1 ≤ u ≤ 4y 1/2 / log y, y ≥ 2, with c 1 a constant. And Xuan [12] (Corollary 1) showed that if D 2 > 0 is fixed and (a, q) = 1, then…”
Section: Preliminary Lemmasmentioning
confidence: 99%
“…holds uniformly in the range 1 ≤ u ≤ 4y 1/2 / log y, y ≥ 2, with c 1 a constant. And Xuan [12] (Corollary 1) showed that if D 2 > 0 is fixed and (a, q) = 1, then…”
Section: Preliminary Lemmasmentioning
confidence: 99%